Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Organisasi Pada Eramart Timbau Tenggarong - Fitriani, Nur Isma; Iskandar, Iskandar (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2020)
Abstract: The purpose of this study was to determine and study the influence of the variables of intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) on employee organizational performance at the Eramart Timbau Tenggarong Minimarket. The sample in this study were 26 employees of the Eramart Timbau Tenggarong Minimarket. The sampling technique was random sampling. The analytical tool used is multiple regression equations with hypothesis testing used F and t tests. The results of the F test calculation obtained that Emotional intelligence and spiritual intelligence simultaneously are able to show their influence on employee performance at the Eramart minimarket. The three independent variables are able to explain changes in employee performance by 84.2% (Adjusted R square = 0.842) while the remaining 15.2% is influenced by other variables not included in this study such as career development, compensation, job stress. From the three results of the t test above, it can be seen that the partial correlation value of the spiritual intelligence variable is the greatest compared to the intellectual intelligence and emotional intelligence variables, which is 0.617 or 61.7%, so that the spiritual intelligence variable is the most dominant variable affecting the employee performance at the Eramart Timbau Tenggarong minimarket. From this description, it can be concluded that the second hypothesis is rejected. Keywords: Intellectual Intelligence, Emotional Intelligence, Performance Spiritual Intelligence, Organizational Performance